PENGARUH JOB INSECURITY DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN BAGIAN SALES PADA PT SUKA FAJAR CABANG SOLOK - Mia Kurnia; Rini Sarianti; Yuki Fitria (Universitas Negeri Padang, 2019)
This study aims to obtain empirical evidence of the influence of job insecurity and job satisfaction on the turnover intention of sales department employees at PT Suka Fajar Padang Branch. In this study, a sample of 64 sales employees at PT Suka Fajar Ltd, Solok Branch was used. To get information and data, a questionnaire was distributed. The analytical method used to prove the truth of the hypothesis is by using path analysis. The results of the analysis show that job insecurity has a positive and significant effect on the turnover intention of sales department employees in PT Suka Fajar Branch of Solok, while job satisfaction has a negative and significant effect on the turnover intention of sales department employees at PT Suka Fajar Solok Branch.Keywords: Job Insecurity, Kepuasan Kerja, Turnover Intention